2021
DOI: 10.1108/ajems-04-2021-0146
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric and threshold effects of public debt on economic growth in SADC: a panel smooth transition regression analysis

Abstract: PurposeThis study aims to interrogate dynamic asymmetric relationships between public debt and economic growth in Southern African Developing Communities (SADC), over the period 2000–2018.Design/methodology/approachThe study employed a panel smooth transition regression (PSTR) technique to analyse dynamic asymmetric relationships between public debt and economic growth, and the threshold effect at which public debt hampers economic growth.FindingsThe findings indicate that there is a significant nonlinear effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Their results indicated a positive relationship between government debt and economic growth. The study by Makhoba et al (2022aMakhoba et al ( , 2022b) contradicts the study by Yang et al (2022) in the case of China. The work documented by Makhoba et al (2022aMakhoba et al ( , 2022b selected emerging and frontier SADC countries using the symmetric transition regression model and found an inverted-shape relationship between debt and growth in the case of South Africa.…”
Section: Empirical Literaturementioning
confidence: 84%
See 3 more Smart Citations
“…Their results indicated a positive relationship between government debt and economic growth. The study by Makhoba et al (2022aMakhoba et al ( , 2022b) contradicts the study by Yang et al (2022) in the case of China. The work documented by Makhoba et al (2022aMakhoba et al ( , 2022b selected emerging and frontier SADC countries using the symmetric transition regression model and found an inverted-shape relationship between debt and growth in the case of South Africa.…”
Section: Empirical Literaturementioning
confidence: 84%
“…The study by Makhoba et al (2022aMakhoba et al ( , 2022b) contradicts the study by Yang et al (2022) in the case of China. The work documented by Makhoba et al (2022aMakhoba et al ( , 2022b selected emerging and frontier SADC countries using the symmetric transition regression model and found an inverted-shape relationship between debt and growth in the case of South Africa. Meanwhile, for Botswana, Namibia, Zambia and Zimbabwe, they found a U-shape relationship between debt and growth.…”
Section: Empirical Literaturementioning
confidence: 84%
See 2 more Smart Citations
“…The study showed that external debt servicing exert negative influences on economic growth while the effect of investment on growth was positive. Makhoba et al (2021) examined the dynamic asymmetric relationships between public debt and economic growth in Southern African Developing Communities (SADC), over the period of 2000-2018. The low-debt regime was found to be positive and statistically significant, while the high-debt regime was detrimental for long-term growth.…”
Section: Empirical Literaturementioning
confidence: 99%